GAMBARAN PELAKSANAAN FISIOTERAPI DADA TERHADAP PENCEGAHAN PNEUMONIA PASIEN TERPASANG VENTILATOR DI RUANGAN INTENSIF RUMAH SAKIT SANTA ELISABETH MEDAN. - Erna Manik; Paska R Situmorang (STIKes Santa Elisabeth Medan, 2017)
.Associated Ventilator Pneumonia (VAP) is a pneumonia that occurs > 48 -72 hours, and the second cause of Health Associated Infection (HAI). The study revealed10% - 20% of patients attached to the ventilator developed into pneumonia. Surveillance shows HAI pneumonia causing death by about 10%. Currently, there is no definite research on the number of VAP incidents in Indonesia. However, research at Dr. Rumkital. The prediction of the number of patients in the Intensive Care Unit (ICU) installed is 148 people and 100 people died with pneumonia. One of the management of nursing patients is ventilator and pneumonia is to do chest physiotherapy. This case study was conducted especially in patients attached to intensive ventilator (ICU). Goals: The Objective of this case study is to determine the description of the implementation of chest physiotherapy on prevention of pneumonia patients by using ventilator in intensive room at Santa Elisabeth Hospital Medan. Method : This case study is in descriptive design by using 20 respondents ie nurses in the ICU room using evaluation sheets and using informed consent sheets as a form of approval. The results of the case study is to illustrate that the implementation of chest physiotherapy performed in the ICU room with good category of 65%, enough 25%, and less 10%. Result : The results of this case study, not much different from the results of previous research by Hendra that was VAP occurred 70% according to the procedure and 40% of custom room SOP. Conclusion : Chest physiotherapy is one of the nursing interventions to prevent the occurrence of VAP.